2023
DOI: 10.1002/nsg.12282
|View full text |Cite
|
Sign up to set email alerts
|

Realistic simulation of GPR for landmine and IED detection including antenna models, soil dispersion and heterogeneity

Sam Stadler,
Stephan Schennen,
Thomas Hiller
et al.

Abstract: Ground‐penetrating radar (GPR) is an effective tool for detecting landmines and improvised explosive devices (IEDs), and its performance is strongly influenced by subsurface properties as well as the characteristics of the target. To complement or replace labour‐intensive experiments on test sites, cost‐efficient electromagnetic wave propagation simulations using the Finite‐Difference Time‐Domain (FDTD) method are being increasingly used. However, to obtain realistic synthetic data, accurate modelling of signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The use of robots [10] and handheld sensors [11] is particularly important here. In the context of humanitarian demining, a landmine leads to specific spatial reflection signatures in the GPR raw data, as shown in [12][13][14]. A system that applies a similar measurement method is ground-penetrating synthetic aperture radar (GPSAR), which uses a more advanced signal processing procedure following a synthetic aperture radar (SAR) approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of robots [10] and handheld sensors [11] is particularly important here. In the context of humanitarian demining, a landmine leads to specific spatial reflection signatures in the GPR raw data, as shown in [12][13][14]. A system that applies a similar measurement method is ground-penetrating synthetic aperture radar (GPSAR), which uses a more advanced signal processing procedure following a synthetic aperture radar (SAR) approach.…”
Section: Introductionmentioning
confidence: 99%
“…Here, it was shown that the trained least squares support vector machine (LS-SVM) was capable of transferring the learned model to other measurement environments by only using a rather limited amount of new training data. In [13], a total of five different landmines were modeled. The IEDs were modeled, for instance, as plastic canisters filled with the explosive material.…”
Section: Introductionmentioning
confidence: 99%